(untitled) (Bangladesh Journal of Animal Science, 2018)
The experiment was conducted to find out the effect of different levels of bottle gourd leaf extraction on beef meatballs. Ground beef samples were divided into four treatment groups having bottle gourd leaf extracts as control T1 (0%), T2 (1%), T3 (2%), T4 (3%). Proximate analysis, sensory tests (color, flavor, tenderness, juiciness, and overall acceptability), cooking loss, pH value, free fatty acids (FFA), thiobarbituric acid values (TBARS), peroxide value (POV) and microbiological examination were determined. Days of intervals of experiment were 0, 15th, 30th and 45th days. Data were analyzed using SAS Statistical software. DM content of all the treatment groups differ significantly (p<0.05). In contrast, DM content increased significantly (p<0.05) with the advancement of different days of intervals. The CP and EE content at different treatment levels differ significantly (p<0.05). The FFA, TBARs, POV values were decreased significantly (p<0.05). The color, flavor, tenderness, juiciness, overall acceptability, raw and cooked pH were increased at different treatment levels significantly (p<0.05). The cooking loss (%) with the advancement of days of intervals were differ significantly (p<0.05). TCC (log CFU/g) and TYMC (log CFU/g) were decreased significantly (p<0.05) at different treatment levels. Parameters studied showed that, 2% bottle gourd leaf extract added meat balls were the best quality, so it may be concluded that 2% bottle gourd leaf extract can be used in beef meatball as a source of antioxidant and antimicrobial agent to increase shelf-life of meatballs. Bang. J. Anim. Sci. 2018. 47 (2):105-113